2018
DOI: 10.1007/978-3-319-91689-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and the Role of Hybridization in Speciation

Abstract: Human beings have a strong, innate desire to classify and name things. We like things to be clear-cut. The way we approach classification of birds is as good an example as any of this. So it always comes as something of a surprise to non-ornithologists to learn that how we classify birds at the level of the species around us is still subject of so much at times fiery debate. Various chapters in this book approach this from different perspectives. In this chapter, the focus is on reminding us that evolution is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 166 publications
0
10
0
Order By: Relevance
“…Literature is growing rapidly on the genomics of speciation and introgression. A facet of this that we focus on here concerns mitochondrial DNA introgression and the mitonuclear discordance it can generate (Rheindt & Edwards, 2011; Winger & Bates, 2015; Roux et al., 2016; Bonnet, Leblois, Rousset, & Crochet, 2017; Gompert, Mandeville, & Buerkle, 2017; Ottenburghs et al, 2015; Ottenburghs et al, 2017;Joseph, 2018; Taylor & Larson, 2019; Peñalba, Joseph, & Moritz, 2019 and references in each). Two principal mechanisms are used to explain a particular form of mitonuclear discordance, that of the capture and replacement of one mitochondrial genome by another: adaptive, mitonuclear interactions, or neutral demographic processes accompanying a range invasion of one taxon or population by another (Currat, Ruedi, Petit, & Excoffier, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Literature is growing rapidly on the genomics of speciation and introgression. A facet of this that we focus on here concerns mitochondrial DNA introgression and the mitonuclear discordance it can generate (Rheindt & Edwards, 2011; Winger & Bates, 2015; Roux et al., 2016; Bonnet, Leblois, Rousset, & Crochet, 2017; Gompert, Mandeville, & Buerkle, 2017; Ottenburghs et al, 2015; Ottenburghs et al, 2017;Joseph, 2018; Taylor & Larson, 2019; Peñalba, Joseph, & Moritz, 2019 and references in each). Two principal mechanisms are used to explain a particular form of mitonuclear discordance, that of the capture and replacement of one mitochondrial genome by another: adaptive, mitonuclear interactions, or neutral demographic processes accompanying a range invasion of one taxon or population by another (Currat, Ruedi, Petit, & Excoffier, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The western clade included all other sampled populations. Nucleotide divergences between each of the three clades of between 3.01 ± 0.87% and 4.56 ± 1.39% are levels typical of species-rank distinction in birds (Avise & Walker 1998, Joseph & Omland 2009, Hung et al 2016, Joseph 2018. Accordingly, and with statistically validated phenotypic correlation among larger groups, three species and seven distinct populations were identified within the complex, thus: 1.…”
Section: Resultsmentioning
confidence: 96%
“…Evidence of hybrid zone movement has been identified in a number of species to date (e.g. Buggs 2007; Carling and Zuckerberg 2011; review in Joseph 2018). In the case of the Passerina bunting hybrid zone, movement was accompanied by a narrowing of width (Carling and Zuckerberg 2011), and ecological, demographic and behavioural factors were cited as potential explanations for the change.…”
Section: Discussionmentioning
confidence: 99%
“…Eastern yellow robin Eopsaltria australis : Morales et al 2017a, b; Red-backed fairy-wren Malurus melanocephalus : Baldassarre et al 2014; Variegated Fairy-wren Malurus lamberti : McLean et al 2017a, b) and regions (Penalba et al 2017). Published genomic studies in general have also been found to focus predominantly on passerines (Joseph 2018; Toews et al 2016).…”
Section: Introductionmentioning
confidence: 99%